2014
DOI: 10.1016/j.vaccine.2013.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines against gonorrhea: Current status and future challenges

Abstract: Gonorrhea occurs at high incidence throughout the world and significantly impacts reproductive health and the spread of human immunodeficiency virus. Current control measures are inadequate and seriously threatened by the rapid emergence of antibiotic resistance. Progress on gonorrhea vaccines has been slow; however, recent advances justify significant effort in this area. Conserved vaccine antigens have been identified that elicit bactericidal antibodies and, or play key roles in pathogenesis that could be ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
101
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 101 publications
4
101
0
Order By: Relevance
“…Among the 28 antigens that were discovered and that elicited bactericidal antibodies against group B meningococci in vitro were the Neisserial heparin-binding antigen (NHBA), factor H-binding protein (fHbp), and the Neisserial adhesin A (NadA). These three proteins are formulated as part of the Bexsero meningococcal group B vaccine approved by the European commission in 2013 and the United States in February of 2015 (12,15,16). Unfortunately, N. gonorrhoeae homologs of these proteins are not suitable vaccine targets (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 28 antigens that were discovered and that elicited bactericidal antibodies against group B meningococci in vitro were the Neisserial heparin-binding antigen (NHBA), factor H-binding protein (fHbp), and the Neisserial adhesin A (NadA). These three proteins are formulated as part of the Bexsero meningococcal group B vaccine approved by the European commission in 2013 and the United States in February of 2015 (12,15,16). Unfortunately, N. gonorrhoeae homologs of these proteins are not suitable vaccine targets (17).…”
mentioning
confidence: 99%
“…Unfortunately, N. gonorrhoeae homologs of these proteins are not suitable vaccine targets (17). Further, in contrast to meningococcal vaccines, progress on gonococcal vaccines has been hampered primarily by the absence of a vaccine-targetable surface capsule, exceptional variability of several surface antigens, a poor understanding of protective responses, and until relatively recently, the lack of a small laboratory animal model to systematically test potential vaccine candidates (16). However, recent potential breakthroughs-such as the availability of transgenic mice to alleviate some host restrictions, new insights into immunosuppression mechanisms used by N. gonorrhoeae, and growing evidence that induction of Th1 response may be critical for vaccine efficacy-justify re-visiting gonorrhea vaccine development and initiating a significant focus in this area (16, 18 -20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also demonstrated that the gonococcus proactively skews the host response away from humoral immunity and toward innate immunity, which is to the pathogen's advantage (9). New vaccine development strategies will likely include immunomodulatory therapy along with presentation of conserved surface antigens in an effort to develop a protective response (10). Thus, the identification of potential vaccine targets remains imperative.…”
mentioning
confidence: 99%
“…Gonorrhea can cause acute urethritis in males and cervicitis in females and lead to sequelae such as pelvic inflammatory syndrome, ectopic pregnancy, sterility, and, through vertical transmission, infant blindness [2]. There is no vaccine for gonorrhea, and antibiotic-resistant N. gonorrhoeae strains are emerging, raising global public health concern [3,4].…”
mentioning
confidence: 99%